Goat Grazing for Restoring, Managing, and Conserving “Satoyama”, a Unique Socio-Ecological Production Landscape - Yayota, Masato; Doi, Kazuya (Frontiers in Sustainable Food Systems, 2020)
Agricultural intensification and socioeconomic changes over several decades have generated many abandoned fields. These changes have led to reduce plant and animal biodiversity, as well as associated loss of ecosystem services, and represent deterioration of a unique socio-ecological production landscape known as “Satoyama” in Japan. Appropriate management measures should be implemented to restore these abandoned fields. The objectives of this study were to: 1) determine the effect of goat grazing on vegetation dynamics and animal performance in response to different stocking rates over a five-year period; and 2) evaluate the economic potential of weed management through goat grazing by comparing this method to mowing with a brush cutter. We found that goat grazing changed vegetational composition, increased the number of plant species, and improved plant diversity in the abandoned field, although stocking rate had little effect on plant diversity. Goat grazing changed vegetation quality, even though goats maintained their nutritional status and body weight over five years. Goat grazing showed economic advantages over mowing during a relatively short period (up to 8–12 days per 1,000 m2). Overall, we found that goats would be ecologically and economically useful in restoring, managing, and conserving agricultural fields. However, a more comprehensive approach is still necessary for conserving “Satoyama”. Combination of grazing, mowing with a machine and prescribed burning may be more effective, and animal and biofuel production in these field would be a solution for reducing field abandonment.